NEET youth and political participation. The contribution of socio-spatial youth work to enhance political participation. - Sailer, Baldur; Tamesberger, Dennis (Momentum Quarterly, 2013)
Young people are one of the most vulnerable groups during the current financial and economic crisis. The amount of young people who are not integrated in the European labour market is a serious concern for democracies. In this context the focus has been directed at the ‘NEET’ indicator. NEET stands for Not in Employment, Education or Training and means that young people are not integrated in the education system and in the labour market. The experience of disintegration can also lead to less political participation. This article argues that disintegrated youth can be reached through open children- and youth work and secondly the disintegrated youth can be supported in an adequate way concerning their difficult histories. Thirdly the article shows that open children and youth work has also a positive effect on the political participation of disintegrated youth. In that context we are talking about socio-spatial youth work and present the theoretical basics of it.
Keywords: NEET-youth; disintegration; socio-spatial youth work; participation; youth unemployment